PENINGKATAN KESELAMATAN DI RUAS JALAN PANTURA KM 46–47 KECAMATAN PATROL KABUPATEN INDRAMAYU - Arivia Shehera Kurniastuti; Novita Sari; Sulistyo Sutanto (Jurnal Transportasi, 2021)
Abstract The number of traffic accidents that occur in Indramayu Regency continues to increase and causes many casualties and material losses. From the available data, it is known that there is one road section which is an accident-prone area, namely the North Coast Java Road section, KM 46-47, which is located in Patrol District, Indramayu Regency. The flow and speed of traffic on this road is quite high, because of its function as a primary arterial road. This study aims to improve safety on the North Coast Java Road section, KM 46-47. The method used is in the form of observation and field data collection. Furthermore, the data obtained is processed, analyzed, and followed by formulating appropriate recommendations. This study shows that the main cause of accidents is the human factor, especially those related to high traffic speeds. To improve the existing conditions, it is proposed to provide road equipment, especially traffic signs, which are adjusted to the stopping sight distance required by motorized vehicles using the road. In addition, it is necessary to apply speed management as part of efforts to improve traffic safety. Keywords: traffic accident; stopping sight distance; road equipment, traffic speed; traffic signs. Abstrak Angka kecelakaan lalu lintas yang terjadi di Kabupaten Indramayu terus meningkat dan menyebabkan banyak korban jiwa dan kerugian material. Dari data yang ada diketahui bahwa terdapat satu ruas jalan yang termasuk daerah rawan kecelakaan, yaitu ruas Jalan Pantai Utara Jawa, KM 46-47, yang terletak di Kecamatan Patrol, Kabupaten Indramayu. Arus dan kecepatan lalu lintas di ruas jalan tersebut cukup tinggi, karena fungsinya sebagai jalan arteri primer. Studi ini bertujuan untuk meningkatkan keselamatan di ruas Jalan Pantai Utara Jawa KM 46-47. Metode yang digunakan berupa observasi dan pengumpulan data lapangan. Selanjutnya data yang diperoleh diolah, dianalisis, kemudian dirumuskan rekomendasi yang tepat. Studi ini menunjukkan bahwa faktor penyebab kecelakaan yang utama adalah faktor manusia, khususnya yang berhubungan dengan kecepatan lalu lintas yang tinggi. Untuk memperbaiki kondisi yang ada, diusulkan pemberian perlengkapan jalan, khususnya rambu lalu lintas, yang disesuaikan dengan jarak pandang henti yang diperlukan oleh kendaraan bermotor yang melintasi jalan tersebut. Selain itu perlu diterapkan manajemen kecepatan sebagai bagian upaya meningkatkan keselamatan lalu lintas. Kata-kata kunci: kecelakaan lalu lintas; jarak pandang henti; perlengkapan jalan, kecepatan lalu lintas; rambu lalu lintas.